Model on Learning of The Fiqh Taharah and Clean Culture in the Islamic Boarding School Environment in Madura - Mukhid, Abd.; Susilowatik, Susilowatik; Jannah, Miftahul; Laili, Sulfatul; Hasna, Ulfatul (Journal of Educational Management and Strategy, 2022)
This study aims to analyze the learning of fiqh taharah and the cultivation of a clean environmental culture using the CIPP (Context, Input, Process, Product) evaluation model. The focus of the research lies in the application of the CIPP evaluation model in the context of learning fiqh taharah in Islamic boarding schools in Madura. The pesantren that became the background of the research included, Miftahul Ulum Islamic Boarding School, Al-Falah Sumber Gayam Islamic Boarding School, Al-Amien Prenduan Islamic Boarding School, Mambaul Ulum Islamic Boarding School Bata-Bata Pamekasan, Nubdatul Bayan Palduding Islamic Boarding School, Nurul Hidayah Islamic Boarding School, Al-Ittihad Al-Islami Islamic Boarding School Camplong Lacquer. This type of research is an evaluative research using a qualitative descriptive approach. The data collection technique uses content analysis from existing data through interviews, observations, and documentation. The results of this study indicate that students have a positive perception, students’ perception about the use of online learning in English learning during the coronavirus disease pandemic based on the assignment has a positive perception. Abstrak Penelitian ini bertujuan untuk menganalisis pembelajaran fiqh taharah dan penanaman budaya lingkungan bersih dengan model evaluasi CIPP (Context, Input, Process, Product). Fokus penelitian terletak pada penerapan model evaluasi CIPP dalam konteks pembelajaran fiqh taharah di pondok pesantren di Madura. Pesantren yang menjadi latar belakang penelitian antara lain, Pesantren Miftahul Ulum, Pesantren Al-Falah Sumber Gayam, Pesantren Al-Amien Prenduan, Pesantren Mambaul Ulum Bata-Bata Pamekasan, Pesantren Nubdatul Bayan Palduding , Pesantren Nurul Hidayah, Pesantren Al-Ittihad Al-Islami Camplong Lacquer. Jenis penelitian ini adalah penelitian evaluatif dengan menggunakan pendekatan deskriptif kualitatif. Teknik pengumpulan data menggunakan analisis isi dari data yang ada melalui wawancara, observasi, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa siswa memiliki persepsi yang positif, persepsi siswa tentang penggunaan pembelajaran online dalam pembelajaran bahasa Inggris selama pandemi penyakit coronavirus berdasarkan tugas memiliki persepsi yang positif.